Life-threatening giant esophageal neurofibroma with severe tracheal stenosis: a case report - Eisuke Booka; Mitsuhide Kitano; Yutaka Nakano; Koki Mihara; Shin Nishiya; Ryo Nishiyama; Shintaro Shibutani; Tomohisa Egawa; Atsushi Nagashima (Surgical Case Reports, 2018)
Abstract Background Benign esophageal tumors are relatively rare, and a neurofibroma in the esophagus is extremely rare. Dysphagia is the most common clinical manifestation in patients with esophageal neurofibroma, and no cases of giant esophageal neurofibroma with severe tracheal stenosis have been reported. Case presentation A 73-year-old woman presented with shortness of breath, and computed tomography scan exhibited a giant mediastinal tumor causing severe tracheal stenosis. An upper gastrointestinal endoscopy revealed a giant submucosal lesion without mucosal changes located 18–23 cm from the incisor teeth. 18F-fluorodeoxyglucose (FDG)-positron emission tomography image revealed an upper mediastinal homogeneous mass and left supraclavicular lymph node with increased FDG accumulation. We performed endoscopic ultrasound-guided fine-needle aspiration biopsy; however, a definitive diagnosis could not be determined. During further investigation, her shortness of breath suddenly worsened and she suffered from wheezing. Because of risk of smothering, we decided to perform quasi-urgent lifesaving surgery. Under the preparation of extracorporeal membrane oxygenation (ECMO) when tracheal intubation fails, bronchial blocker was inserted over the tracheal stenosis and the left-lung ventilation was performed via intubation alone. Under general anesthesia, the patient was placed in the left lateral position and we performed right thoracotomy. The tumor strongly adhered to the trachea; however, the trachea or recurrent laryngeal nerves were not damaged in the surgery. Following esophagectomy, we performed gastric conduit reconstruction through the posterior mediastinum, and hand-sewn anastomosis was performed in the left neck. Immunohistochemical staining was positive for S-100 but negative for c-KIT, CD34, α-SMA, and desmin; these morphological and immunohistochemical characteristics were consistent with the diagnosis of neurofibroma. Conclusions It is often difficult to diagnose esophageal neurofibroma preoperatively. The preparation of ECMO could be considered in patients with severe airway obstruction for safe tracheal intubation. This is the first case of life-threatening giant esophageal neurofibroma with severe tracheal stenosis.